FIELD HOCKEY INJURIES AMONG HIGH SCHOOL GIRLS IN THE UNITED STATES, 2008/09–2015/16. Issue 4 (1st February 2017) - Pierpoint, Lauren; Comstock, Rae Dawn
Abstract : Background: Although women's field hockey is a popular sport world-wide, detailed epidemiological injury data on United States (US) high school players are sparse. Characterizations of injury rates and patterns in high school athletes is the first necessary step to drive targeted injury prevention efforts. Objective: Describe rates and patterns of high school field hockey injuries. Design: Retrospective descriptive epidemiology. Setting: US High Schools. Patients(or Participants): Injured high school field hockey athletes. Interventions (or Assessment of Risk Factors): Athlete exposure (AE) and injury event data reported by athletic trainers to a large national high school sports-related injury surveillance system. Main Outcome Measurements: Injury rates and patterns. Results: From 2008/09–2015/16, 1, 256 injuries were sustained during 723, 026 AEs for a rate of 1.74/1, 000 AE. Injury rates were significantly higher in competitions (2.64) than practices (1.32) (rate ratio=2.00, 95% CI=1.79–2.23). Neither practice nor competition injury rates changed significantly over time (p>0.05). Overall, most injuries were due to contact with a playing apparatus (20.0% contact with ball; 15.9% contact with stick). The most common injury mechanism during practice was non-contact (32.2%) but during competition was contact with a playing apparatus (49.9%). The most common injuries were concussions (15.5%) and hip/thigh/upper leg strains (13.1%); eye injuries were uncommon (0.8%). Most concussions occurred during competition (77.1%) and were due to contact with a playing apparatus (50.0%) or contact with another player (39.5%). Most athletes returned to play within 3 weeks (81.8%); 3.8% of injuries resulted in medical disqualifications for the remainder of the season. Surgical repair was required in 4.1% of injuries; specifically, 16.7% of knee injuries and 12.8% of fractures. Conclusions: Field hockey injury rates and patterns differ between competition and practice. Injury prevention efforts should focus on reducing contact with the ball and stick, especially during competitions, while preserving the integrity of the game.